Challenges in Diagnosing Gallbladder Tuberculosis Mimicking Acute Calculus Cholecystitis: A Case Report of an Uncommon Presentation - Munira, Sirajam; Hasan, Mehedi; Jolil, Rukshana; Sarwar, Jahangir Md (Bangladesh Journal of Medicine, 2024)
Gall bladder tuberculosis (TB) represents a highly uncommon form of extrapulmonary TB, even within endemic regions, presenting a considerable diagnostic challenge. Limited pre-operative diagnostic tools lead to cholecystectomy and tissue analysis to initiate definitive treatment, thereby prolonging patient suffering and delaying diagnosis. A 50-year-old menopausal lady presented with history of prolonged fever, significant weight loss, and subsequent upper abdominal pain. Serological and blood biochemistry tests revealed normal findings, except for moderate anemia. Abdominal ultrasound detected cystitis, while MRCP revealed a distal common bile duct stricture concomitant with gallstones. However, ERCP failed to confirm the biliary stricture, instead revealing papillary stenosis. The initial diagnosis was cholelithiasis, leading to laparoscopic cholecystectomy. The histopathological examination of the specimen indicated the presence of granulomas consisting of epithelioid cells and multinucleated giant cells. Additionally, areas of necrosis and chronic inflammatory cell infiltration were observed within the gallbladder wall. Histopathology of Lymph node biopsy showed granulomas, multinucleated giant cells, and areas of necrosis. Category-1 Anti-Tubercular Therapy was initiated postoperatively, resulting in favorable clinical and operative outcomes. Although gall bladder TB is a rare entity, clinicians should raise a high index of suspicion for TB in patients presenting with prolonged fever, weight loss, and features suggestive of calculus cholecystitis in endemic areas, aiming to mitigate unnecessary investigations and treatments, particularly in resource-limited settings such as Bangladesh. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation: 168-169.